IMPLEMENTASI JARINGAN SYARAF TIRUAN DENGAN ALGORITMA PERCEPTRON DALAM PENENTUAN PROGRAM STUDI MAHASISWA BARU: Artificial Neural Network (ANN);Determination Of The Study Program;Implementation;Matlab;Perceptron. - Kahar, Novhirtamely; Aritonang, Widya (JURNAL AKADEMIKA, 2022)
The determination of the study program is important for prospective students to enter state universities and private universities this is because it is a decision to hone, explore the abilities of each prospective student and reduce students who fail or drop out. This research is expected so that students know the appropriate study program based on their abilities. The data inputted is personal data of prospective students, average values, majors and test scores with Alternative study programs, namely study programs at the Faculty of Computer Science and The output of the data processed is in the form of results about selected study programs. The method used by researchers is the perceptron method, Perceptron is one of the simple ANN training methods used the first training algorithm procedure. It consists of a single neuron with synaptic weights that is regulated using the hard limit activation function. After an analysis of the ANN simulation of the perceptron algorithm with Matlab in determining the majors, the results of the perceptron method were obtained, namely the perceptron method was able to determine the target output and actual output as much as54.28%.